Art of Tradition: The Armenian Gospel Books (Seventeenth Century) in the Gulbenkian Collection - Grigoryan, Hermine; Miranda, Maria Adelaide; Sargsyan, Lusine; Rodrigues, Jorge; Matevosyan, Karen; Melo, Maria João (Studia Ceranea, 2025)
This paper presents preliminary notes on three seventeenth-century Armenian Gospel Books preserved in the Calouste Gulbenkian Museum in Lisbon. For the first time, these manuscripts are examined through a comprehensive art-historical lens, with attention also given to their codicological and material features. These codices attest to an unbroken manuscript tradition flourishing within the Armenian diaspora communities of Constantinople, Isfahan/New Julfa, and Crimea during the seventeenth century. Their production history and the art of their illuminations reveal both the social demand for such works and the enduring artistic preferences rooted in the medieval legacy of Armenian manuscript culture.